GENERASI ALPHA: DAMPAK PENGGUNAAN GAWAI SELAMA MASA PANDEMI COVID-19 - Mellyan (Pusat Studi Gender dan Anak, 2021)
Gadgets have become an important necessity in the digital age. This phenomenon not only occurs among adults but also in children. The youngest generation today is known as Gen A or Alpha generation. experts predict this generation is most familiar with technology, especially during the Covid-19 pandemic so it needs guidance from older people because children will not gain social-emotional abilities if only interact with the device. The purpose of this study is to explain the influence of devices used in the lives of the Alpha generation during the Covid-19 pandemic. Research methods use qualitative methods, with descriptive approaches and data collection methods of research libraries. Research shows that the challenges of educating children are becoming increasingly complicated, especially during the Covid-19 pandemic. 29% AUD in 2020 in Indonesia using gadgets. This is due to changes in learning methods that occur during pandemics, as well as parents who let children play with gadgets without proper control, then they experience addiction, thus affecting motor, cognitive, and psychological development, as well as creativity. Screen time excessive risk experiencing speech delay, disturbance, weakness social skill and even brain damage. On the other hand, gadgets have a positive impact such as adding science and entertainment. Parents play an important role in controlling children in the use of gadgets so that they avoid addiction to give birth to the golden generation in the future.